Neuroprotection by Paeoniflorin against Nuclear Factor Kappa B-Induced Neuroinflammation on Spinal Cord Injury. (2nd December 2018) - Wang, Bin; Dai, Wangying; Shi, Lijun; Teng, Honglin; Li, Xigong; Wang, Jing; Geng, Wujun
Abstract : Background. Acute spinal cord injury (SCI) is one of the most common and devastating causes of sensory or motor dysfunction. Nuclear factor-kappa B(NF- κ B)-mediated neuroinflammatory responses, in addition to nitric oxide (NO), are key regulatory pathways in SCI. Paeoniflorin (PF), a major active component extracted from Paeonia roots, has been suggested to exert neuroprotective effects in the central nervous system. However, whether PF could improve the motor function after SCI in vivo is still unclear. Method. Immunohistochemical analysis, western blot, real-time quantitative PCR, immunofluorescence staining, and histopathological and behavioral evaluation were used to explore the effects of paeoniflorin after SCI for 14 days. Results. In this study, PF treatment significantly inhibited NF- κ B activation and downregulated the expression of inducible nitric oxide synthase (iNOS), cyclooxygenase-2(COX-2), and Nogo-A. Comparing behavioral and histological changes in SCI and PF treatment groups, we found that PF treatment improved motor function recovery, attenuated the histopathological damage, and increased neuronal survival in the SCI model. PF treatment also reduced expression levels of Bax and c-caspase-3 and increased the expression level of Bcl-2 and cell viabilities. Upregulation of TNF- α, IL-6, and IL-1 β after injury was also prevented by PF. Conclusion. These results suggest that the neuroprotective effects of PF are related to the inhibition of the NF- κ B signaling pathway. And PF may be a therapeutic strategy in spinal cord injury.